KEANEKARAGAMAN JENIS DAN KARAKTERISTIK HABITAT MAMALIA KECIL PASCAERUPSI TAHUN 2010 DI LERENG SELATAN GUNUNG MERAPI - , ALVIO RAHMA RAMADHAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
After the Merapi volcano eruption in 2010, the wildlife habitat in south slope of Mount Merapi area has been damaged. The impact of damage can be classified into mild, moderate and heavy damage impacts which potentially affect the small mammals population and their microhabitat. Small mammals are important for their roles in ecological processes as seed disperser. This position creates interactions between small mammals and their environment that might be affected by the damage. The purpose of this study was to determine small mammals diversity and investigate the characteristics of habitat in the South Slope of Mount Merapi National Park after the eruption of Mount Merapi in 2010. The research used descriptive and qualitative method. Systematic sampling method was applied to place traps of small mammals on location for diversity data. Habitat variable data was collected by a circular plot in same location as the trap. Small mammals diversity were analyzed using Shannon Diversity Index (H ') . Habitat variables data were analyzed using a difference test with SPSS version 16. The results showed that the species diversity of small mammals consists of Pacific rat ( Rattus exulans ) and Malaysian field rats ( Rattus tiomanicus ). Shannon Diversity Index ( H ' ) on the mild damage were 0.24 and 0.27 in heavy damage inside national park area and 0.26 ( moderate and heavy damage ) outside of the park. This results explain that the characteristic of small mammals habitats which affect the presence and the number of individuals are shrub cover , altitude , and overstory tree size .